The imaginary museum of musical works an essay in the philosophy of music - Goehr, Lydia; Oxford eBooks (Oxford : Clarendon, 1992)
What is the difference between a performance of Beethoven's Fifth Symphony and the symphony itself? Lydia Goehr combines philosophical and historical methods of enquiry to show that a historical perspective is indispensable to a full understanding of musical ontology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Music -- Philosophy and aesthetics; Electronic books